The ASSOCIATION OF SMOKING HISTORY WITH TREATMENT DURATION IN PATIENTS WITH PULMONARY TUBERCULOSIS IN INPATIENT WARD AT GENERAL HOSPITAL EAST JAKARTA INDONESIA 2025: Smooking history with coorelation pulmonary tuberculosis - Gea, Nurti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Pulmonary tuberculosis (TB) is a contagious infectious disease that remains a global and national health problem. Indonesia is among the eight countries with the highest TB burden in the world. The success of pulmonary TB treatment is greatly influenced by patient adherence to the 6–9-month therapy regimen. One factor associated with influencing the duration of treatment is smoking. Smoking can damage the lungs’ defense mechanisms, impair mucociliary function, and weaken the immune system, potentially slowing the healing process and increasing the risk of treatment discontinuation. The high prevalence of smokers in Indonesia makes this factor important to study, particularly among pulmonary TB patients undergoing inpatient care. Objective: This study aims to determine the relationship between smoking history and treatment duration among pulmonary TB patients in the Edelweis Barat inpatient ward at Budhi Asih Regional General Hospital, East Jakarta, in 2025. Methods: This study employed a cross-sectional design with a quantitative correlational approach. Sampling was conducted using probability sampling via simple random sampling, involving 76 respondents. Data were collected via a questionnaire and analyzed using the Chi-Square statistical test. Results: The results of the study showed that respondents with moderate and high smoking behavior were equally represented, with 38 respondents (50%) in each group. The most common duration of treatment was >9 months, with 28 respondents (36.8%), followed by 6–9 months with 25 respondents (32.9%), and 0–6 months with 23 respondents (30.3%). Most respondents with high smoking behavior had a treatment duration of >9 months, totaling 28 respondents (73.7%). The Chi-Square test results showed a p-value of 0.001, indicating a significant association between smoking history and treatment duration in pulmonary TB patients. Conclusion: There is a significant association between smoking history and treatment duration in pulmonary TB patients. High smoking behavior tends to be associated with longer treatment duration.